A novel heteroacene 2-(perfluorophenyl)-1H-imidazo[4, 5-b]phenazine for selective sensing of picric acid. Issue 44 (18th April 2016) - Gu, Pei-Yang; Wang, Chengyuan; Nie, Lina; Long, Guankui; Zhang, Qichun
Abstract : A novel chemosensor probe (PFIPZ ) has been successfully synthesized and can identify picric acid over other electron-deficient compounds or strong acids. Abstract : A novel sensing probe, 2-(perfluorophenyl)-1 H -imidazo[4, 5- b ]phenazine (PFIPZ ) containing imidazole and phenazine units, has been successfully synthesized and can identify picric acid over other electron-deficient compounds or strong acids.